TI_GERICHTE 60.2007.362 vom 29. Oktober 2007 , Istanza di ricusa nei confronti del giudice della Pretura penale. tempestività - TI Tribunale d'appello (2007)
Istanza di ricusa nei confronti del giudice della Pretura penale. tempestività